Slurry, capillary structure and manufacturing method of capillary structure
By using slurry containing components such as stainless steel powder and forming capillary structures through printing and vacuum sintering technology, the problem that existing stainless steel heat-smooth plate capillary structure preparation is difficult to meet high-performance heat dissipation, and excellent capillary effect and fluid transmission performance are achieved.
Patent Information
- Application Number
- CN202510069499.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
AI Technical Summary
The existing stainless steel heat-smoothing plates have limitations in capillary structure preparation and are difficult to meet the needs of high-performance heat dissipation.
A slurry containing stainless steel powder, solvent, thickener, dispersant and pore-forming agent is used, and a capillary structure is formed by printing technology.
The formation of stainless steel capillary structures with specific structures and properties improves capillary effect and fluid transmission performance, and meets the needs of high-performance heat dissipation.
Smart Images

Figure BDA0005245284480000071 
Figure BDA0005245284480000072 
Figure BDA0005245284480000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of capillary structures, and in particular to a slurry, a capillary structure and a manufacturing method thereof. Background Art
[0002] With the rapid development of modern electronic technology, the trend of electronic equipment becoming thinner and smaller has become an irreversible trend. This trend not only requires electronic equipment to have higher performance, but also puts forward more stringent requirements on its heat dissipation components. Among the many heat dissipation components, the vapor chamber (VC) is highly favored due to its efficient heat dissipation performance.
[0003] A vapor chamber is a vacuum chamber with a microstructure, usually made of copper. It is flat and has an upper and lower cover that fits tightly together. The interior is supported by metal columns and filled with a working medium. When the heat source is transferred to the evaporation zone of the vapor chamber, the coolant in the chamber vaporizes in a low vacuum environment, absorbs heat energy and expands rapidly, filling the entire chamber. Subsequently, the gaseous cooling medium condenses when it contacts the colder area, releasing the accumulated heat energy, and flows back to the evaporation heat source with the help of the microstructured capillary channels, thus forming a repetitive heat cycle in the chamber.
[0004] However, although the traditional copper vapor chamber has excellent heat dissipation performance, it is expensive and the process is complicated. In recent years, stainless steel vapor chambers have gradually emerged as an emerging technology with significant advantages such as simple process, low cost, and high strength. However, stainless steel vapor chambers still have limitations in the preparation of capillary structures. At present, the capillary structure in copper vapor chambers is mainly prepared by sintering copper powder and copper powder mesh, while stainless steel vapor chambers mainly use metal mesh to prepare capillary structures. Due to the structural characteristics of the stainless steel mesh itself, its capillary capacity is relatively limited, and it is difficult to meet the needs of high-performance heat dissipation.
[0005] In order to solve at least one of the above technical problems, the present invention provides a slurry, a capillary structure and a manufacturing method thereof. Summary of the invention
[0006] The object of the present invention is to provide a slurry, a capillary structure and a method for making the same, which can form a stainless steel capillary structure with specific structure and performance.
[0007] The purpose of the present invention is achieved by the following technical solutions:
[0008] In a first aspect, the present invention provides a slurry, the components of which include:
[0009] Stainless steel powder;
[0010] Solvents;
[0011] Thickeners;
[0012] Dispersants;
[0013] Pore forming agent.
[0014] The above scheme has the beneficial effect that the slurry can form a capillary structure with specific structure and performance by including stainless steel powder, solvent, thickener, dispersant and pore former. The stainless steel powder provides structural strength, the solvent helps the slurry to be evenly coated, the thickener controls the fluidity of the slurry, the dispersant ensures the uniform dispersion of the stainless steel powder in the solvent, and the pore former forms pores during the sintering process, thereby giving the capillary structure the capillary effect required.
[0015] Further, the content of the stainless steel powder is: 30wt%-75wt%; and / or,
[0016] The content of the solvent is: 20wt%-50wt%; and / or,
[0017] The content of the thickener is: 0.1wt%-2wt%; and / or,
[0018] The content of the dispersant is: 0.1wt%-0.5wt%; and / or,
[0019] The content of the pore former is 5wt%-20wt%.
[0020] The beneficial effects of the above scheme are: the content range of each component is clarified to ensure the stability and processing performance of the slurry. The appropriate solvent content is conducive to the coating and drying of the slurry, the content of the thickener and dispersant controls the viscosity and dispersion effect of the slurry, and the content of the pore-forming agent affects the porosity and capillary performance of the final capillary structure.
[0021] Further, the stainless steel powder is selected from one or more combinations of 201, 304L, 316L, 403, and 904L;
[0022] Further, the solvent is selected from a combination of one or more of water, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, propylene glycol monomethyl ether, ethylene glycol, and propylene glycol;
[0023] Further, the thickener is selected from one or more combinations of lithium magnesium silicate, magnesium aluminum silicate, fumed silica, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose;
[0024] Further, the dispersant is selected from one or more combinations of Tween reagents;
[0025] Furthermore, the pore-forming agent is polymethyl methacrylate microspheres and / or polystyrene microspheres.
[0026] The above scheme has the beneficial effect of selecting specific types of stainless steel powder, solvent, thickener, dispersant and pore-forming agent, which have excellent physical and chemical properties and can meet the requirements of capillary structure for material properties. For example, 316L stainless steel powder has good corrosion resistance and strength, propylene glycol and dipropylene glycol methyl ether as solvents have low toxicity and good volatility, hydroxypropyl cellulose as thickener can provide stable viscosity control, Tween 80 as dispersant has good dispersing effect, and polystyrene microspheres as pore-forming agent can form a uniform and stable pore structure.
[0027] Furthermore, the stainless steel powder is 316L;
[0028] Further, the solvent is propylene glycol and / or dipropylene glycol methyl ether;
[0029] Further, the thickener is hydroxypropyl cellulose;
[0030] Further, the dispersant is Tween 80;
[0031] Furthermore, the pore-forming agent is polystyrene microspheres.
[0032] The above scheme has the beneficial effect that the performance of the capillary structure can be optimized by further limiting the types of slurry components. For example, the use of 316L stainless steel powder can improve the corrosion resistance and strength of the structure, propylene glycol and dipropylene glycol methyl ether as solvents can ensure uniform coating and rapid drying of the slurry, hydroxypropyl cellulose as a thickener can provide stable viscosity, Tween 80 as a dispersant can ensure uniform dispersion of stainless steel powder, and polystyrene microspheres as pore-forming agents can form a uniform and fine pore structure.
[0033] Furthermore, the size of the stainless steel powder is 100-2000 mesh;
[0034] Furthermore, the size of the pore-forming agent is 10-100 μm.
[0035] The beneficial effect of the above scheme is that by controlling the size of stainless steel powder and pore former, the pore size and distribution of the capillary structure can be further controlled. The size of stainless steel powder affects the density and strength of the structure, and the size of pore former directly affects the size and shape of the pores, thereby affecting the capillary effect and fluid transmission performance.
[0036] Furthermore, the size of the stainless steel powder is 800 mesh and / or 500 mesh;
[0037] Furthermore, the size of the pore former is 50 μm.
[0038] The beneficial effect of the above scheme is that stainless steel powder and pore former of specific size can form a capillary structure with specific pore structure and performance. For example, 800 mesh and 500 mesh stainless steel powder can provide appropriate structural strength, while 50 μm pore former can form a uniform and fine pore structure, thereby optimizing the capillary effect and fluid transmission performance.
[0039] In a second aspect, the present invention provides a method for manufacturing a capillary structure, the method comprising:
[0040] The slurry was printed on a stainless steel cover plate and a capillary structure was obtained by vacuum sintering;
[0041] Wherein, the slurry is the slurry mentioned above.
[0042] The beneficial effect of the above scheme is that the capillary structure is obtained by printing the slurry on the stainless steel cover plate and vacuum sintering, which is simple, efficient and easy to control. The printing technology can ensure the uniform coating of the slurry, and the vacuum sintering can ensure the density and strength of the structure while forming the desired pore structure.
[0043] Further, the slurry is printed on the stainless steel cover plate to a thickness of 50-200 μm;
[0044] Furthermore, during the vacuum sintering process: the heating rate is 3-6°C / min, the sintering temperature is 900-1300°C, and the sintering time is 4-10h.
[0045] The beneficial effects of the above scheme are: clarifying the parameters such as the slurry printing thickness and the heating rate, sintering temperature and sintering time during the vacuum sintering process, which have an important influence on the formation and performance of the capillary structure. Appropriate printing thickness can ensure the uniform coating of the slurry and the structural strength after sintering, and reasonable sintering parameters can ensure the density of the structure and the formation of the pore structure.
[0046] Furthermore, the slurry was printed on a stainless steel cover plate with a thickness of 70 μm;
[0047] Furthermore, during the vacuum sintering process: the heating rate is 5°C / min and the sintering temperature is 1000°C.
[0048] The beneficial effect of the above scheme is that the specific parameters of the slurry printing and vacuum sintering process can further optimize the performance of the capillary structure. For example, a printing thickness of 70 μm can provide appropriate structural thickness and strength, and a heating rate of 5 ° C / min and a sintering temperature of 1000 ° C can ensure uniform sintering of the structure and the formation of a porous structure.
[0049] In a third aspect, the present invention provides a capillary structure, wherein the capillary structure is made of the above-mentioned slurry.
[0050] The beneficial effect of the above scheme is that the capillary structure made by the above slurry and manufacturing method has excellent capillary effect and fluid transmission performance. The structure can be used in various applications requiring capillary action, such as liquid filtration, liquid transmission, thermal management and other fields.
[0051] Compared with the prior art, the beneficial effects of the present invention include at least:
[0052] The slurry of the present invention can form a stainless steel capillary structure with specific structure and performance. Specifically, the stainless steel powder provides structural strength, the solvent helps the slurry to be evenly coated, the thickener controls the fluidity of the slurry, the dispersant ensures the uniform dispersion of the stainless steel powder in the solvent, and the pore former forms pores during the sintering process, thereby giving the capillary structure the capillary effect required. DETAILED DESCRIPTION
[0053] Example embodiments will now be described more fully. However, example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; on the contrary, these embodiments are provided to make the present invention more comprehensive and complete and to fully convey the concept of example embodiments to those skilled in the art.
[0054] The words expressing position and direction described in the present invention may also be changed as needed, and all such changes are included in the protection scope of the present invention.
[0055] The slurry of the present invention comprises stainless steel powder, solvent, thickener, dispersant and pore former. When used, the slurry of the present invention can form a stainless steel capillary structure with specific structure and performance. In practical application, the stainless steel powder provides structural strength, the solvent helps the slurry to be evenly coated, the thickener controls the fluidity of the slurry, the dispersant ensures the uniform dispersion of the stainless steel powder in the solvent, and the pore former forms pores during the sintering process, thereby giving the capillary structure the capillary effect required.
[0056] In some embodiments, the content of the stainless steel powder is 30wt%-75wt%, for example, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 45wt%, 50wtwt%, 55wt%, 60wt%, 65wt%, 70wt% or 75wt%. The content of the solvent is 20wt%-50wt%, for example, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 33wt%, 35wt%, 38wt%, 40wt%, 43wt%, 45wt%, 48wt% or 50wt%. The content of thickener is 0.1wt%-2wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2.0wt%. The content of dispersant is 0.1wt%-0.5wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%. The content of the pore-forming agent is 5wt%-20wt%, for example: 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%.
[0057] When applying, clarifying the content range of each component can ensure the stability and processing performance of the slurry. The appropriate solvent content helps the coating and drying of the slurry, the content of the thickener and dispersant controls the viscosity and dispersion effect of the slurry, and the content of the pore-forming agent affects the porosity and capillary performance of the final capillary structure.
[0058] In some other embodiments, the stainless steel powder is selected from one or more combinations of 201, 304L, 316L, 403, and 904L models, and is purchased from Changsha Tianjiu Metal Materials Co., Ltd. The size of the stainless steel powder is 100-2000 mesh, for example: 100 mesh, 200 mesh, 300 mesh, 400 mesh, 500 mesh, 600 mesh, 700 mesh, 800 mesh, 900 mesh, 1000 mesh, 1100 mesh, 1200 mesh, 1300 mesh, 1400 mesh, 1500 mesh, 1600 mesh, 1700 mesh, 1800 mesh, 1900 mesh or 2000 mesh. The solvent is selected from one or more combinations of water, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, propylene glycol monomethyl ether, ethylene glycol, and propylene glycol, and is purchased from Wuxi Best Chemical Co., Ltd. The thickener is selected from one or more combinations of lithium magnesium silicate, aluminum magnesium silicate, fumed silica, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose, and is purchased from Shandong Chengxin Chemical Technology Co., Ltd. The dispersant is selected from one or more combinations of Tween reagents, and is purchased from Shandong Chengxin Chemical Technology Co., Ltd. The pore former is polymethyl methacrylate microspheres and / or polystyrene microspheres, and is purchased from Dongguan Baolimei Plastic Co., Ltd. The size of the pore former is 10-100 μm, for example: 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.
[0059] When applying, the selection of specific types of stainless steel powder, solvent, thickener, dispersant and pore-forming agent can meet the requirements of capillary structure for material properties. For example, 316L stainless steel powder has good corrosion resistance and strength, propylene glycol and dipropylene glycol methyl ether as solvents have low toxicity and good volatility, hydroxypropyl cellulose as a thickener can provide stable viscosity control, Tween 80 as a dispersant has a good dispersion effect, and polystyrene microspheres as a pore-forming agent can form a uniform and stable pore structure.
[0060] In practical applications, the pore size and distribution of the capillary structure can be further controlled by controlling the size of the stainless steel powder and the pore former. The size of the stainless steel powder affects the density and strength of the structure, and the size of the pore former directly affects the size and shape of the pores, thereby affecting the capillary effect and fluid transmission performance.
[0061] In some preferred embodiments, the stainless steel powder is 316L model, and the size of the stainless steel powder is 800 mesh and / or 500 mesh. The solvent is propylene glycol and / or dipropylene glycol methyl ether. The thickener is hydroxypropyl cellulose. The dispersant is Tween 80. The pore-forming agent is polystyrene microspheres, and the size of the pore-forming agent is 50 μm.
[0062] When applied, the use of 316L stainless steel powder can improve the corrosion resistance and strength of the structure, propylene glycol and dipropylene glycol methyl ether as solvents can ensure uniform coating and rapid drying of the slurry, hydroxypropyl cellulose as a thickener can provide stable viscosity, Tween 80 as a dispersant can ensure uniform dispersion of stainless steel powder, and polystyrene microspheres as pore-forming agents can form a uniform and fine pore structure. Therefore, further limiting the types of slurry components can optimize the performance of the capillary structure.
[0063] In practical applications, 800-mesh and 500-mesh stainless steel powders can provide appropriate structural strength, while 50μm pore formers can form uniform and fine pore structures, thereby optimizing capillary effects and fluid transmission performance. Therefore, further limiting the specific sizes of stainless steel powders and pore formers can form capillary structures with specific pore structures and performances.
[0064] Furthermore, the present invention can print the above-mentioned slurry on a stainless steel cover plate and obtain a capillary structure through vacuum sintering.
[0065] When applied, printing technology can ensure uniform coating of the slurry, and vacuum sintering can ensure the density and strength of the structure while forming the desired pore structure.
[0066] In some embodiments, the slurry is printed on the stainless steel cover plate with a thickness of 50-200 μm to ensure uniform coating of the slurry and structural strength after sintering. For example: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm. In addition, during the vacuum sintering process: the compactness of the structure and the formation of the pore structure are ensured by controlling the sintering parameters. Specifically, the heating rate is 3-6 ° C / min, for example: 3 ° C / min, 4 ° C / min, 5 ° C / min or 6 ° C / min. The sintering temperature is 900-1300 ° C, for example: 900 ° C, 1000 ° C, 1100 ° C, 1200 ° C or 1300 ° C. The sintering time is 4-10 hours, for example: 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0067] In some preferred embodiments, in order to provide appropriate structural thickness and strength, the thickness of the slurry printed on the stainless steel cover plate is 70 μm. In order to ensure uniform sintering of the structure and the formation of the pore structure, during the vacuum sintering process: the heating rate is 5°C / min and the sintering temperature is 1000°C.
[0068] In summary, the present invention aims to provide a printable stainless steel capillary slurry, by configuring the slurry into a printing paste, and using a screen printer to print a capillary structure of the required thickness onto the cover plate of the heat spreader. Subsequently, through processes such as laser welding or vacuum sintering, the capillary structure printed on the cover plate is tightly combined with the cover plate to form a stainless steel heat spreader with excellent heat dissipation performance. Not only does it achieve the preparation of the capillary structure of the stainless steel heat spreader, but it also improves the overall heat dissipation capacity of the heat spreader, providing strong heat dissipation support for the thinness and miniaturization of electronic equipment.
[0069] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail with examples and comparative examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0070] The thickener of the embodiment of the present invention is added to the solvent and stirred evenly using a high-speed disperser to obtain a first mixture. The stirring frequency is 30 Hz and the stirring time is 2 hours. Then, the dispersant, pore-forming agent and stainless steel powder are added to the first mixture, and the high-speed disperser is continued to be stirred evenly to obtain a slurry. The stirring frequency is 30 Hz and the stirring time is 2 hours. Then, the obtained slurry is printed on a stainless steel cover plate and vacuum sintered to evaporate the solvent in the paste and carbonize the binder to form a stable stainless steel capillary structure, and the capillary structure is sintered on the cover plate. Finally, the cover plate with sintered stainless steel capillary structure is used to assemble the heat spreader.
[0071] The slurry formula, printing process and sintering process of the embodiments of the present invention can form a stable and non-removable stainless steel capillary structure on the stainless steel cover plate. The stainless steel capillary structure can maintain integrity and avoid collapse in the stage from printing to vacuum sintering; and after vacuum sintering, it can be firmly combined with the cover plate and is not easy to fall off. Specifically, the slurry parameters and manufacturing process parameters of Examples 1-6 of the present invention are detailed in Table 1. The performance parameters of the stainless steel capillary structure obtained in Examples 1-6 are detailed in Table 2.
[0072] Table 1 Slurry and manufacturing process parameters of some examples
[0073]
[0074] Table 2 Performance parameters of capillary structures obtained in some examples
[0075]
[0076]
[0077] Among them, VC is a heat sink.
[0078] Comparative Example 1:
[0079] A stainless steel mesh with a size of 200 mesh, a thickness of 70 μm, and a model of 304L is used as a stainless steel capillary structure, and the stainless steel mesh is welded to the stainless steel cover plate by laser welding technology. The heat sink is assembled using the stainless steel cover plate welded with the stainless steel mesh. The performance parameters of the stainless steel capillary structure obtained in this comparative example are detailed in Table 3.
[0080] In comparative example 1, although laser welding can ensure a firm bond between the steel mesh and the cover plate, the process cost may be high. Combining Table 2 and Table 3, it can be seen that the average pore size of the stainless steel mesh in comparative example 1 is relatively large, which affects the efficiency of the capillary effect. In addition, the heat source temperature of VC at a power of 5W is slightly higher than that of the embodiment, indicating that there is a certain gap in heat dissipation efficiency.
[0081] Table 3 Performance parameters of the capillary structure obtained in the comparative example
[0082]
[0083] Comparative Example 2:
[0084] A copper mesh with a size of 200 mesh and a thickness of 70 μm was taken as a copper mesh capillary structure, and sintered at 950°C for 2 hours in a nitrogen-hydrogen mixture (10% hydrogen) to sinter the copper mesh capillary structure onto a copper cover plate. A heat spreader was assembled using the copper cover plate with the sintered copper mesh capillary structure. The performance parameters of the stainless steel capillary structure obtained in this comparative example are detailed in Table 3.
[0085] Combining Table 2 and Table 3, it can be seen that Comparative Example 2 is similar to Comparative Example 1, and the average pore size of the copper mesh is larger, which affects the efficiency of the capillary effect.
[0086] Comparative Example 3:
[0087] The difference between Comparative Example 3 and Example 1 is that:
[0088] (1) The stainless steel powder was replaced with copper powder, and the size of the copper powder was 500 mesh.
[0089] (2) Sintering technology: sintering at 950°C for 2 hours in a nitrogen-hydrogen mixture (10% hydrogen).
[0090] The performance parameters of the copper powder capillary structure obtained in this comparative example are shown in Table 3.
[0091] From Table 1, Table 2 and Table 3, it can be seen that by printing the slurry of the present application on a stainless steel cover plate to obtain a stainless steel capillary structure, a stainless steel VC with better performance than a steel mesh can be obtained. The stainless steel capillary structure of the present application has an adjustable pore size, which is better than the capillary capacity of the steel mesh, and provides a new solution for improving heat dissipation capacity.
[0092] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the invention without departing from the principles and purpose of the present invention. All such changes should fall within the scope of protection of the claims of the present invention.
Claims
1. A slurry, characterized in that: The components of the slurry include: Stainless steel powder; Solvents; Thickeners; Dispersants; Pore forming agent.
2. The slurry according to claim 1, characterized in that The content of the stainless steel powder is: 30wt%-75wt%; and / or, The content of the solvent is: 20wt%-50wt%; and / or, The content of the thickener is: 0.1wt%-2wt%; and / or, The content of the dispersant is: 0.1wt%-0.5wt%; and / or, The content of the pore former is 5wt%-20wt%.
3. The slurry according to claim 1, characterized in that The stainless steel powder is selected from one or more of 201, 304L, 316L, 403, and 904L; and / or, The solvent is selected from a combination of one or more of water, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, propylene glycol monomethyl ether, ethylene glycol, and propylene glycol; and / or, The thickener is selected from one or more combinations of lithium magnesium silicate, magnesium aluminum silicate, fumed silica, bentonite, polyamide wax, methyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose; and / or, The dispersant is selected from one or more combinations of Tween reagents; and / or, The pore-forming agent is polymethyl methacrylate microspheres and / or polystyrene microspheres.
4. The slurry according to claim 1, characterized in that The stainless steel powder is 316L type; and / or, The solvent is propylene glycol and / or dipropylene glycol methyl ether; and / or, The thickener is hydroxypropyl cellulose; and / or, The dispersant is Tween 80; and / or, The pore-forming agent is polystyrene microspheres.
5. The slurry according to claim 1, characterized in that The size of the stainless steel powder is 100-2000 mesh; and / or, The size of the pore former is 10-100 μm.
6. The slurry according to claim 1, characterized in that The size of the stainless steel powder is 800 mesh and / or 500 mesh; and / or, The size of the pore former is 50 μm.
7. A method for manufacturing a capillary structure, characterized in that: The production method comprises: The slurry was printed on a stainless steel cover plate and a capillary structure was obtained by vacuum sintering; Wherein, the slurry is the slurry described in any one of claims 1-6.
8. The method for manufacturing a capillary structure according to claim 7, characterized in that: The slurry is printed on the stainless steel cover plate to a thickness of 50-200 μm; and / or, During the vacuum sintering process, the heating rate is 3-6°C / min, the sintering temperature is 900-1300°C, and the sintering time is 4-10h.
9. The method for manufacturing a capillary structure according to claim 7, characterized in that: The slurry is printed on the stainless steel cover plate to a thickness of 70 μm; and / or, During the vacuum sintering process, the heating rate is 5°C / min and the sintering temperature is 1000°C.
10. A capillary structure, characterized in that: The capillary structure is made of the slurry described in any one of claims 1-6.